Pengaruh Brand Image dan Kualitas Produk Terhadap Keputusan Pembelian Produk Makanan Pada UMKM di Lapangan Brawijaya Kota Surabaya - Sintiah, Lailatus Sharifa Alif; Moch. Khoirul Anwar (Jurnal Ekonomika dan Bisnis Islam, 2024)
Micro, small and medium enterprises in Brawijaya Field have become culinary tourism attractions that attract many visitors, so many business people have decided to set up MSMEs to earn income. Due to the large number of business actors there, competition results in the products being sold having similarities with other business actors, starting from the brand to the quality of the products being sold. This research aims to determine the influence of brand image and product quality on purchasing decisions. The data collection method uses a Likert scale and is analyzed using multiple linear regression. The sample was determined using a purposive sampling technique of 100 respondents. Based on the results of the T test and F test analysis that have been carried out, it shows that brand image and product quality partially and simultaneously have a positive and significant effect on purchasing decisions. Based on the coefficient of determination, brand image and product quality variables influence purchasing decisions by 54%. The results of this study emphasize the importance of brand image and product quality as key elements that merchants must prioritize to increase sales.